AI COMPANION ADOPTION TO ADDRESS DIGITAL ANXIETY: A QUANTITATIVE STUDY OF GENERATION Z - Hary Firmansyah; Depy Muhamad Pauzy; Gian Riksa Wibawa; Dudu Risana (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This quantitative study aims to examine the effect of AI companion adoption on digital anxiety among Generation Z. The study used a survey-based approach with 100 respondents, measuring AI companion adoption through indicators of emotional attachment, perceived ease of interaction, conversational naturalness, frequency of daily AI conversational use, and interface comfort, while digital anxiety was assessed through concerns about data privacy, over-reliance, discomfort with more private interactions, and distrust of AI reliability. The findings in this study indicate that AI companion adoption has a significant positive effect on digital anxiety. This suggests that greater reliance on AI as a social surrogate increases users' concerns about privacy violations, loss of human connection, and intense reliance on artificial intelligence. However, the regression model only demonstrated moderate explanatory power, suggesting that other factors also contribute to digital anxiety. These results imply that although Generation Z finds emotional comfort and conversational ease with AI, AI development companies should prioritize transparent data policies, ethical AI design, and digital literacy programs to mitigate anxiety. This study contributes to the growing discourse on human-AI interactions by highlighting the dual nature of AI companions that offer emotional support while simultaneously triggering psychological discomfort related to safety and social surrogacy.